Factors influencing smoking cessation brief intervention implementation among dentists - Dr Sarah Ng; Associate Professor Shilpi Ajwani; Dr Trupta Desai (Elsevier, 2023)
Aim or Purpose: To investigate factors influencing the low uptake of smoking cessation brief interventions (COHS, 2021), despite high prevalence of smokers amongst the patient population within the public dental system (AIHW, 2022, SLHD, 2019). Materials and Methods: It was a mixed-method low-negligible risk research of a convergent-parallel mixed method design. Data collection methods included semi-structured interviews with eight Sydney Local Health District (SLHD) Community Oral Health Clinic (COHC) dentists, and clinical record analysis of fifty patient records from SLHD COHCs. Each interview transcript was coded for thematic analysis, and data items from the clinical record analysis were analysed using descriptive statistics. The study was approved by SLHD Ethics Committee. Results: From clinical record audits, although 84% completed the 'Ask' step of the smoking cessation brief intervention, less than 10% undertook the 'Advise' and 'Act' steps. Factors identified as influencing smoking cessation brief intervention implementation included the characteristics of patients, the oral health status of patients, and dentist-perceived barriers. Nature of public patients, types of clinical services provided, and lack of training and time were some of the key reasons identified during dentist interviews. Conclusions: A flexible and tailored intervention approach suited to both the clinicians and intended audience is required, especially in priority populations seen in public dental clinics who experience more significant difficulty with accomplishing a sustained smoking cessation intervention.